2014
DOI: 10.1063/1.4871782
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics and mass transport mechanisms of GaN columns by selective area metal organic vapor phase epitaxy

Abstract: Articles you may be interested inReal-time x-ray studies of crystal growth modes during metal-organic vapor phase epitaxy of GaN on c-and mplane single crystals Appl. Phys. Lett. 105, 051602 (2014); 10.1063/1.4892349Surface diffusion and layer morphology of ( ( 11 2 ¯ 2 ) ) GaN grown by metal-organic vapor phase epitaxyIn situ spectroscopic ellipsometry study of GaN nucleation layer growth and annealing on sapphire in metalorganic vapor-phase epitaxy J. Appl. Phys. 98, 033522 (2005);Three-dimensional GaN colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…SiN x is formed on the sidewall with necessary condition, which is not likely within the growth window for GaN nanorods. Wang et al reported that the silane flux does not influence the diffusion length of species on substrate, while has much more effect on that of the sidewall [8]. The vertical growth rate of nanorods increases 3 times when the silane flux increases from 16.5 to 165 nmol/min.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…SiN x is formed on the sidewall with necessary condition, which is not likely within the growth window for GaN nanorods. Wang et al reported that the silane flux does not influence the diffusion length of species on substrate, while has much more effect on that of the sidewall [8]. The vertical growth rate of nanorods increases 3 times when the silane flux increases from 16.5 to 165 nmol/min.…”
Section: Introductionmentioning
confidence: 94%
“…In the continuous growth mode a lot of parameters were studied on the morphology and uniformity of nanorods, such as V/III ratio, temperature, polarity, carrier gas and doping, etc [11e14]. Growth kinetics and mass transport mechanisms of GaN nanorods are demonstrated by some reports [1,3,8]. The silane is often used to form a vertical nanorod.…”
Section: Introductionmentioning
confidence: 99%
“…However, the PL intensity decreased as the SiH 4 flow increased, indicating the reduced crystal quality of the GaN microrods [21]. To date, the majority of 3D GaN structures fabricated by selective area growth (SAG) have involved MOCVD with a continuous flux [21][22][23] or pulse-mode growth [12,[24][25][26], and MBE [27]. In contrast, there have been few reports on the growth of 3D GaN structures by SAG-HVPE because of the difficulty in achieving elongated structures [28].…”
Section: Introductionmentioning
confidence: 96%
“…Koester et al showed that a SiH 4 flow can play an important role in enhancing the axial growth rate [10]. However, the PL intensity decreased as the SiH 4 flow increased, indicating the reduced crystal quality of the GaN microrods [21]. To date, the majority of 3D GaN structures fabricated by selective area growth (SAG) have involved MOCVD with a continuous flux [21][22][23] or pulse-mode growth [12,[24][25][26], and MBE [27].…”
Section: Introductionmentioning
confidence: 98%
“…As a result of the intensive studies, the growth conditions of III-V NW have been found. Also, the following facts regarding the impact of the mask size and pitch on the NW morphology have been estimated: (i) at the mask edges, the NW growth rate is usually several times higher than that in the middle part of the mask [3,4]; (ii) the NW growth rate decreases with the increase of the mask window size [1,5]; (iii) the increase of the mask pitch p leads to the increase [6] or decrease [1] of the NW length. The first dependence is explained by the additional gas-phase and surface fluxes of species from the area without the mask windows to the NW array [3,4].…”
Section: Introductionmentioning
confidence: 99%